Psychology and Mental Health 2016
DOI: 10.4018/978-1-5225-0159-6.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Computational Intelligence Paradigms

Abstract: The evolution of communication networks and information systems, to support wireless access, cloud and grid computing, and big data, provides great business opportunities. However, it also generates a new trend of sophisticated network threats and offers several challenges in securing information and systems confidentiality, integrity and availability. The traditional techniques used by security experts are mostly static and lack the much needed characteristics of adaptation and self-organization, computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Carbon tetrachloride was obtained from Aldrich Chemical Co. (Milwaukee, Wl, USA), Synthesis of dihydrothymoquinone: Dihydrothymoquinone (DHTQ) was repared from TQ by reduction with sodium hydrosulfite according to the procedure of (7). The structure of DHTQ was confirmed by Infra red spectroscopy and the purity was checked by melting point and thin layer chromatography as described previously (8). The compound was found to be > 99% pure.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon tetrachloride was obtained from Aldrich Chemical Co. (Milwaukee, Wl, USA), Synthesis of dihydrothymoquinone: Dihydrothymoquinone (DHTQ) was repared from TQ by reduction with sodium hydrosulfite according to the procedure of (7). The structure of DHTQ was confirmed by Infra red spectroscopy and the purity was checked by melting point and thin layer chromatography as described previously (8). The compound was found to be > 99% pure.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from primary and secondary amino groups, tertiary amino groups have also been incorporated into cellulose via an ether linkage. Cotton was reacted with b-chloroethyldiethylamine hydrochloride (7) in the presence of sodium hydroxide, producing diethylaminoethylcellulose [45][46][47]. It has been shown that subsequent fixation of triazinyl dyes does not involve quaternisation of the attached diethylamino group [48].…”
Section: Introductionmentioning
confidence: 99%